Implementation of strategies to counteract the consequences of the pandemic in the tourism sector (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the article is to analyze the implementation of strategies to mitigate the socio-economic impact of Covid-19 and restore the tourism sector. Estimates at the national level are quite complex and reflect the scale of the impact on tourism, as well as the challenges associated with predicting a rapidly changing and uncertain situation. Quantifying the current and future impacts of the crisis on tourism is challenging, as the crisis has exposed weaknesses in tourism statistical information systems, including the lack of reliable, comparable and timely data to support political and business decisions. A number of forecasts presented in the spring and summer of 2020 did not come true. Forecasting the impact of the pandemic on the tourism economy is faced with a high degree of uncertainty, a rapidly changing epidemiological situation at the level of national states and regions. The article analyzes the implementation of the main strategies recommended by the UNWTO to overcome the consequences of the pandemic: 1) crisis management and mitigation; 2) providing incentives and accelerating recovery; and 3) preparing for tomorrow and developing tactics to overcome the crisis in the tourism sector using the example of the countries analyzed. The recovery of tourism will depend on the interrelated effects of the economic crisis and the health crisis on overcoming the pandemic, the influence of supply and demand factors. The peculiarity of the current crisis lies in the global nature of its scale, duration, continuing uncertainty and the interconnectedness of economic, social and medical factors of influence.